The innovation ecosystem in rural tourism and hospitality – a systematic review of innovation in rural tourism. Issue 7 (9th November 2021) - Madanaguli, Arun; Kaur, Puneet; Mazzoleni, Alberto; Dhir, Amandeep
Abstract : Purpose: Innovation in rural tourism and hospitality (RT) is a complex process that involves the exchange of knowledge and resources between many actors and the interrelationships between those actors in the business environment. The purpose of this paper is to provide structure to this "knowledge and resource ecosystem" through a thorough systematic review of the extant literature. Design/methodology/approach: The current study uses a time-tested and reproducible systematic literature review process to identify and analyse 79 research papers that have discussed innovation in RT. Findings: Through content analyses, this review identifies critical stakeholders in the innovation ecosystem, as well as the enabling and hindering roles these stakeholders play in innovation. The thematic analysis uncovers three key research foci: stakeholders and their roles, outcomes of innovation and business model innovation. The review also identifies types of innovation and critically analyses the bibliographical research profile. The authors summarise the findings in an RT innovation ecosystem model, which includes the various actors and their knowledge and resource sharing roles within the business environment. Originality/value: This is one of the first systematic reviews to concentrate on RT innovation and, within that focus, on knowledge and resource networks in particular rather than on innovation in tourism in general, which was the focus of prior reviews. The authors encourage cross-pollination of ideas by introducing theories from the strategic management, innovation, knowledge management and business model innovation literature wherever appropriate. To consolidate and present the findings on the innovation process's antecedents and outcomes, the authors present an ecosystem of innovation within the RT framework.